Flip posse - Vargas, Michelle Elaine S.A
Flip Posse is an 8-minute video documentary focusing on the disturbing fact that Filipino gangster in Los Angeles, California do harm to other Filipinos whether gangmates, rival Filipino gangsters or even innocent victims. The documentary takes off from the filmmaker's sentiments about her brother Mike who is a member of Akrho Pinoy. He, along with Arjay of Tau Gamma Pinoy and Mark of Flipside give their reasons for joining the gang. They say it is to fulfill the human need to belong especially in a foreign land. Their reasons are compared to Jeff's, a 28-year-old former active member of the Satanas Gang, one of the first Filipino gangs in Los Angeles. He said the purpose of the gang used to be about protecting Filipinos against other races but this has changed over the years. Today, the Filipino gangster in Los Angeles is capable of harming a rival Filipino gangster, a gangmate and even an ordinary Filipino with nothing to do with a gang. This is illustrated through several cases presented in the documentary. Arjay tells the story of Carlo, a gangmate who got killed during a drive-by shooting. FOX 11 Network News covers an event involving the Asian Boyz Gang which picked on one of their own members at a park in Downey, California. Aurora, now former girlfriend of one this documentary's subjects Arjay, sued him for abuse of former spouse/fiance. This thesis, being personal, wraps up with the filmmaker wishing that her gangster brother Mike will learn from Arjay who is currently in jail. The director used some experimental techniques to keep the viewers interested in the documentary. She felt that such treatment would fit the subject matter. The documentary aims to present to the viewer the irony of the fact that although Filipinos almost automatically bond with fellow Filipinos in a foreign country, here in the documentary, they appear to be capable of harming their kind. They somehow lose their sense of identity and drown in their efforts to "fit in" in a country not theirs.